2015
DOI: 10.1089/scd.2015.0220
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Regulating Impaired Neurogenesis of Fragile X Syndrome Human Embryonic Stem Cells

Abstract: Fragile X syndrome (FXS) is the most common form of inherited cognitive impairment. It is caused by developmental inactivation of the FMR1 gene and the absence of its encoded protein FMRP, which plays pivotal roles in brain development and function. In FXS embryos with full FMR1 mutation, FMRP is expressed during early embryogenesis and is gradually downregulated at the third trimester of pregnancy. FX-human embryonic stem cells (FX-hESCs), derived from FX human blastocysts, demonstrate the same pattern of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 66 publications
4
55
0
Order By: Relevance
“…We functionally identified altered differentiation of a subpopulation of cells in human and mouse FXS neurospheres indicating FXS‐specific changes during early differentiation of neural progenitors. The data are consistent with previous studies which have shown impaired development of human FMRP‐deficient neural cells (Telias et al, ). Differential responses to MPEP in human and mouse progenitors could reflect species‐specific differences but also other progenitor type‐dependent differences, including dissimilar developmental stages of progenitors (Meredith et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…We functionally identified altered differentiation of a subpopulation of cells in human and mouse FXS neurospheres indicating FXS‐specific changes during early differentiation of neural progenitors. The data are consistent with previous studies which have shown impaired development of human FMRP‐deficient neural cells (Telias et al, ). Differential responses to MPEP in human and mouse progenitors could reflect species‐specific differences but also other progenitor type‐dependent differences, including dissimilar developmental stages of progenitors (Meredith et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…A full characterization of the in vitro derived neurons in terms of subtype and degree of maturation were not reported. Another candidate is the SOX family of transcription factors, and in particular SOX9 and SOX2 , which are known for their key role in neurogenesis and are both highly expressed in NPCs [112,113]. By comparing expressions of mature in vitro differentiated neurons and FXS and WT hESCs, Telias et al typically found a drop in FXS NPCs in SOX9 expression levels concurrent with a rise in SOX2 mRNA levels [114].…”
Section: Neurological Pathology In Fxs Neurons Derived From Hpscmentioning
confidence: 99%
“…The canonical Wnt/ β-Catenin signaling pathway has been shown to play pivotal roles in embryonic neural development as well as in adult neurogenesis [1,2]. For example, aberrant regulation of Wnt signaling has been proposed to underlie some of the symptoms observed in Alzheimer's disease, Autism and Fragile X Syndrome [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the effects of CHIR and XAV so far have also been predominantly performed on animal models, and in non-neural tissues. Recently, we reported on the molecular mechanisms regulating impaired in-vitro neural differentiation of Fragile X Syndrome (FXS)-human embryonic stem cells (hESCs), carrying the full mutation at the FMR1 gene [8]. In that study, we hypothesized that dysregulation of Wnt signaling could be responsible for the poor neural differentiation associated with these cells [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation